2016
DOI: 10.1007/s00467-016-3413-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of renal size and function in extremely low birth weight children at 7 and 11 years of age

Abstract: BackgroundThere are a lack of studies describing a longitudinal association between preterm delivery and renal complications later in life. We assessed renal size and function in preterm infants born with extremely low birth weight (ELBW) during 4 years of follow-up, comparing these parameters to age-matched children born full term (term controls).MethodsThe results of selected renal laboratory tests [levels of cystatin C, creatinine, blood urea nitrogen (BUN)] and of renal ultrasound evaluations were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 42 publications
1
52
1
Order By: Relevance
“…In survivors of extreme prematurity, renal structural and functional differences were noted: smaller kidney volume and higher cystatin C and blood urea nitrogen (BUN) were detectable in 7- to 11-year-old former extremely low birth weight (ELBW) infants compared to infants who were born at term [64]. Follow-up at 6 years showed that survivors of prematurity less than 33 weeks had similar rates of microalbuminuria, but those with additional AKI also had a lower GFR than those without AKI [65].…”
Section: Reviewmentioning
confidence: 99%
“…In survivors of extreme prematurity, renal structural and functional differences were noted: smaller kidney volume and higher cystatin C and blood urea nitrogen (BUN) were detectable in 7- to 11-year-old former extremely low birth weight (ELBW) infants compared to infants who were born at term [64]. Follow-up at 6 years showed that survivors of prematurity less than 33 weeks had similar rates of microalbuminuria, but those with additional AKI also had a lower GFR than those without AKI [65].…”
Section: Reviewmentioning
confidence: 99%
“…4 To detect small kidneys, asymmetry, or structural abnormalities, we suggest, if feasible, a baseline renal ultrasound, and follow-up should be performed as indicated [89]. …”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…In a Norwegian population-based study, the odds of a reduced GFR (<100 mL/min) were 1.66 (95% CI, 1.16-2.37) in men and 1.65 (95% CI, 1.17-2.35) in women who were born SGA compared with AGA, which increased further among those who had been very small for gestational age, demonstrating a dose-response effect [32]. Studies examining renal function after preterm birth have thus far been conducted predominantly in children, and many have described an association with reduced GFR and increased urinary albumin excretion among those who had been born preterm [30,31,87,88,89]. In a cohort of young adults born preterm, birth weight correlated negatively with microalbuminuria and positively with GFR [90].…”
Section: Introduction To a Health Problemmentioning
confidence: 99%
“…Following the search strategy described, 248 (232 + 16) hits were analyzed to result in 6 casecontrol and 3 ELBW cohort studies for the analysis [Figure 1]. The key characteristics of the individual case-control studies are provided in Table 1 [12][13][14][15][16][17][18], cohort studies in Table 2 [19][20][21]. Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 19 January 2020 doi:10.20944/preprints202001.0213.v1…”
Section: Resultsmentioning
confidence: 99%
“…One study (Krakow cohort) collected Cys C values in the same cohort at the age of 7 and 11 years, and calculated eGFR values in the latest paper [14,18]. To provide an overview on the characteristics, data (eGFR data calculated) reported at the age of 7 years were added to Besides the GFR values, data on other aspects of renal and general outcome (like renal ultrasound, renal tubular functions, blood pressure, biometry and body composition) were coreported.…”
Section: Resultsmentioning
confidence: 99%